Radiotherapy techniques in irradiation of breast cancer: a dosimetric comparison - Vaz, Bruna (2022)
Radiotherapy in breast cancer is increasingly a common treatment and is mostly prescribed to cancer patients after surgery in an adjuvant treatment.